Experience of initiating collaboration of traditional healers in managing HIV and AIDS in Tanzania - Moshi Mainen J; Mahunnah Rogasian L; Mbwambo Zakaria H; Uiso Febronia C; Kayombo Edmund J; Mgonda Yasin H (BMC, 2007)
Abstract Collaboration between traditional healers and biomedical practitioners is now being accepted by many African countries south of the Sahara because of the increasing problem of HIV/AIDS. The key problem, however, is how to initiate collaboration between two health systems which differ in theory of disease causation and management. This paper presents findings on experience learned by initiation of collaboration between traditional healers and the Institute of Traditional Medicine in Arusha and Dar-es-Salaam Municipalities, Tanzania where 132 and 60 traditional healers respectively were interviewed. Of these 110 traditional healers claimed to be treating HIV/AIDS. The objective of the study was to initiate sustainable collaboration with traditional healers in managing HIV/AIDS. Consultative meetings with leaders of traditional healers' associations and government officials were held, followed by surveys at respective traditional healers' "vilinge" (traditional clinics). The findings were analysed using both qualitative and quantitative methods. The findings showed that influential people and leaders of traditional healers' association appeared to be gatekeepers to access potential good healers in the two study areas. After consultative meetings these leaders showed to be willing to collaborate; and opened doors to other traditional healers, who too were willing to collaborate with the Institute of Traditional Medicine in managing HIV/AIDS patients. Seventy five percent of traditional healers who claimed to be treating HIV/AIDS knew some HIV/AIDS symptoms; and some traditional healers attempted to manage these symptoms. Even though, they were willing to collaborate with the Institute of Traditional Medicine there were nevertheless some reservations based on questions surrounding sharing from collaboration. The reality of past experiences of mistreatment of traditional healers in the colonial period informed these reservations. General findings suggest that initiating collaboration is not as easy as it appears to be from the literature, if it is to be meaningful; and thus we are calling for appropriate strategies to access potential healers targeted for any study designed with sustainability in mind.